Modernity in dispute: The early chilean route to constitutionalism (1823-1833) - Verbal, Valentina (Derecho Público Iberoamericano, 2022)
Intending to define Chile’s route to constitutionalism in the early Chilean republic (1823-1833), this article problematizes two frequent omissions in historiography. The first omission subsumes the period exclusively under the category of liberalism, without considering that two great political forces acted at the time: the conservatives and liberals. The second tends to discount the participation of these two forces in a dispute over two conceptions of modernity: absolutist, which comes from the ancient regime, and alternative, which presupposes a greater exaltation of individuals.